2014
DOI: 10.5194/acp-14-2071-2014
|View full text |Cite
|
Sign up to set email alerts
|

Deposition nucleation viewed as homogeneous or immersion freezing in pores and cavities

Abstract: Abstract. Heterogeneous ice nucleation is an important mechanism for the glaciation of mixed phase clouds and may also be relevant for cloud formation and dehydration at the cirrus cloud level. It is thought to proceed through different mechanisms, namely contact, condensation, immersion and deposition nucleation. Conceptually, deposition nucleation is the only pathway that does not involve liquid water, but occurs by direct water vapor deposition onto a surface. This study challenges this classical view by pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
323
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(338 citation statements)
references
References 179 publications
13
323
1
1
Order By: Relevance
“…The critical embryo radius calculated with CNT can be validated by testing its consistency with the melting and freezing point depression of ice observed in pores of mesoporous silica (Marcolli, 2014). When pores are too narrow to incorporate an ice crystal of critical size, ice will not nucleate.…”
Section: Classical Nucleation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The critical embryo radius calculated with CNT can be validated by testing its consistency with the melting and freezing point depression of ice observed in pores of mesoporous silica (Marcolli, 2014). When pores are too narrow to incorporate an ice crystal of critical size, ice will not nucleate.…”
Section: Classical Nucleation Theorymentioning
confidence: 99%
“…Subcritical ice clusters may be produced at a high rate but are prevented from reaching a critical size by the confinement in the pores. Marcolli (2014) showed that the CNT-based parameterization by Zobrist et al (2007) is able to describe the observed melting point depression in pores as a function of temperature and should therefore be well suited to estimate critical embryo sizes. The critical embryo volume for homogeneous ice nucleation predicted by this parameterization is 109 nm 3 at 254 K and increases to 1441 nm 3 at 265 K. We therefore consider the energy barrier and critical embryo size predicted by CNT as a quantity with a physical basis.…”
Section: Classical Nucleation Theorymentioning
confidence: 99%
“…5 are compared to modeled predictions of pore condensation and freezing (PCF) onsets. 66 Fig . 5 includes the calculated PCF freezing onsets for pore sizes in the ranges of 7.5-15 nm as the light brown colored area.…”
Section: Isothermal Ice Nucleation Experimentsmentioning
confidence: 99%
“…† Recently, it was proposed that deposition ice nucleation on mineral surfaces was likely a homogeneous or immersion freezing of water in pores or cavities. 66 Experimentally derived onset conditions shown in Fig. 5 are compared to modeled predictions of pore condensation and freezing (PCF) onsets.…”
Section: Isothermal Ice Nucleation Experimentsmentioning
confidence: 99%
“…Thus, these results suggest that different x therm or other approaches might be needed within different temperature regimes. Also, deposition nucleation close to water saturation may coincide with pore condensation freezing (Marcolli et al, 2014).…”
Section: Ice Nucleation Active Surface Site Densitiesmentioning
confidence: 99%